2015
DOI: 10.1111/1755-0998.12451
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive transcriptome of early development in yellowtail kingfish (Seriola lalandi)

Abstract: Seriola lalandi is an ecologically and economically important species that is globally distributed in temperate and subtropical marine waters. The aim of this study was to identify large numbers of genic single nucleotide polymorphisms (SNPs) and differential gene expression (DGE) related to the early development of normal and deformed S. lalandi larvae using high-throughput RNA-seq data. A de novo assembly of reads generated 40,066 genes ranging from 300 bases to 64,799 bases with an N90 of 788 bases. Homolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…Although the percentage of unigenes of L. albus with a BLAST-hit may appear to be a relatively small number, we found that this value does not differ from other de novo transcriptome studies with non-model echinoderms14153437. In this sense, the lack of homology with known proteins could be explained by biological reasons such as: i) the lack of annotated protein sequences of phylogenetically close species; ii) sequences from untranslated regions (UTR) of mRNA; iii) long noncoding RNA; and iv) orphan proteins38. These results are congruent to those reported for the transcriptome of the sea urchin S. intermedius 39, the sea star Acanthaster planci 14 and the brittle star Amphiura filiformis 40.…”
Section: Discussionmentioning
confidence: 55%
“…Although the percentage of unigenes of L. albus with a BLAST-hit may appear to be a relatively small number, we found that this value does not differ from other de novo transcriptome studies with non-model echinoderms14153437. In this sense, the lack of homology with known proteins could be explained by biological reasons such as: i) the lack of annotated protein sequences of phylogenetically close species; ii) sequences from untranslated regions (UTR) of mRNA; iii) long noncoding RNA; and iv) orphan proteins38. These results are congruent to those reported for the transcriptome of the sea urchin S. intermedius 39, the sea star Acanthaster planci 14 and the brittle star Amphiura filiformis 40.…”
Section: Discussionmentioning
confidence: 55%
“…Insights into molecular mechanisms may lead to a better understanding of physiological traits such as growth and sex. To date, genetic resources for Seriola species have been developed mainly for yellowtail kingfish and the Japanese yellowtail, including genetic linkage maps [ 9 , 10 ] and a radiation hybrid (RH) map [ 9 ], as well as the production of transcriptome data [ 11 ]. For the greater amberjack, very few molecular resources have been published, but they do include a cytogenetic characterization, which revealed in total 24 mainly acrocentric chromosomes (2n) and, similar to other Carangidae species, no morphologically differentiated sex chromosome [ 12 ].…”
Section: Background Informationmentioning
confidence: 99%
“…Despite the economic importance of Yellowtail kingfish (YTK) Seriola lalandi world-wide (e.g., with a current annual production of about 4,000 tons, valuing 56 million dollars in Australia), there has been very limited published information regarding genetic and genomic architecture for quantitative complex traits in this species. Recent studies generated initial genomic resources to examine genetic diversity of YTK populations ( Premachandra et al, 2017a ; Sepulveda and Gonzalez, 2017 ) or assessing predictive power of statistical models used for genomic selection ( Nguyen et al, 2018 ), as well using transcriptome information to identify genes related to fish immunity ( Jacobson et al, 2017 ) and those involved with skeletal deformity during early growth phase in this species ( Patel et al, 2016 ). To date, only a low-density genetic linkage map was developed for S. lalandi , involving a handful of 217 microsatellites markers ( Ohara et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%